Upaya Peningkatan Kinerja Karyawan di PT. Trikarya Sidoarjo dalam Pembuatan Pintu Press dengan Metode FMEA - Madani, Isfan; Koesdijati, Titiek (Jurnal Ilmiah Wahana Pendidikan, 2023)
PT. Trikarya Sidoarjo is an industry engaged in interior manufacturing design. The production process carried out is HPL (High Perussure Laminates) wood processing which produces home furnishings whose sizes and models are made according to the wishes of consumers. The company has several processing stations including material handling stations, particle wood cutting stations, particle wood molding cutting stations, HPL stations, coating stations, finishing stations, quality control stations, and packaging stations. Efforts to improve employee performance in making press doors using the FMEA method according to implementation and proposals are in making press doors with even conditions and not wavy smoothly according to motifs, press doors ordered according to size, all available facilities are already using machines, security systems work in making press doors already exists, payments via transfer or Q-RIS function properly, payment is provided using cash, employees provide information and solve problems properly, employees serve customers according to procedures and are friendly, employees provide supporting equipment to overcome obstacles occurs in the manufacture of press doors complete with clear information so that customers feel safe and comfortable, employees approach customers who are experiencing difficulties in a friendly manner, employees swiftly solve problems faced by customers and employees listen carefully to customer complaints.